2023
DOI: 10.1002/aur.3005
|View full text |Cite
|
Sign up to set email alerts
|

Bumetanide oral solution for the treatment of children and adolescents with autism spectrum disorder: Results from two randomized phase III studies

Joaquin Fuentes,
Mara Parellada,
Christina Georgoula
et al.

Abstract: The efficacy and safety of bumetanide oral solution for the treatment of autism spectrum disorder (ASD) in children and adolescents was evaluated in two international, multi‐center, randomized, double‐blind, placebo‐controlled phase III trials; one enrolled patients aged 7–17 years (SIGN 1 trial) and the other enrolled younger patients aged 2–6 years (SIGN 2). In both studies, patients were randomized to receive bumetanide oral solution twice daily (BID) or placebo BID during a 6‐month double‐blind treatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Interestingly, urea is not the first diuretic to be tested in ASD. The loop diuretic bumetanide has shown promising results 45,46 for the treatment of ASD, although a recent phase III clinical trial failed to show efficacy 47 . Loop diuretics provoke the elimination of water and salts, with water loss exceeding that of salt, only resulting in moderate hemoconcentration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, urea is not the first diuretic to be tested in ASD. The loop diuretic bumetanide has shown promising results 45,46 for the treatment of ASD, although a recent phase III clinical trial failed to show efficacy 47 . Loop diuretics provoke the elimination of water and salts, with water loss exceeding that of salt, only resulting in moderate hemoconcentration.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that it is worth pursuing this to a Phase 3 development aimed at obtaining market authorization. To align with the requirements of the European Medicine Agency (EMA), this included the entire pediatric population in two separate trials (2-7 and 7-18 years old) [55] . Participants received a bumetanide syrup with a taste agreeable to children /adolescents.…”
Section: Clinical Trials: Success and Failurementioning
confidence: 99%
“…Other studies have shown that bumetanide can reduce cerebral edema and nerve cell injury in rats with focal ischemia-reperfusion injury [16][17][18]. Several clinical studies have been conducted to evaluate the efficacy of bumetanide for spectrum disorder (ASD), Parkinson's disease (PD), and neonatal seizures [19][20][21]. Unfortunately, the results were negative.…”
Section: Introductionmentioning
confidence: 99%